Effect of Simvastatin in Serum Interleukin-6 Level in Patients with Acute Ischemic Stroke - Meo, Maria Lettisia; Machin, Abdulloh; Hasmono, Didik (Folia Medica Indonesiana, 2020)
Acute ischemic stroke is the leading cause of death and causing permanent disability in adults worldwide. In acute ischemic stroke, IL-6 levels positively correlated to more severe neurological deficits, more extensive brain damage and worse prognoses. The use of statin was associated with milder initial stroke severity, better functional outcome and lower mortality. This clinically randomized controlled trial study was aimed to analyze the serum levels of IL 6 in acute ischemic stroke patients who treated with Simvastatin 20 mg compare to placebo. Samples were taken using consecutive sampling method from hospitalized acute ischemic stroke patients in Neurology Department of Dr. Soetomo Teaching Hospital Surabaya and Airlangga University Hospital Surabayafrom August to November 2017. Total of 44 patients met the inclusion criteria, consisting of 22 patients in treatment group and 22 patients in control group.There were no significant difference in the characteristic of the patients in both groups (p>0.05). Averages of serum IL-6 in the control and the treatment group are 38.594±74.313 and 17.760±25.253(p=0,438) while averages of serum IL-6 post in the control group and the treatment are 46.586±103.484 and 15.275±17.183 (p=0,589). There were no significant level escalation in pre and post of control group (p = 0.205) and also no significant level reduction in pre and post of treatment group (p = 0.411), while the average difference in the control group (-7.992 + 78.912 pg/ml) and in the treatment group (2.485 + 23.738 pg/ml).